Dispersive Raman spectroscopy allows the identification and quantification of melanin types. Issue 7 (4th March 2015) - Galván, Ismael; Jorge, Alberto
Abstract Melanins are the most prevalent pigments in animals and are involved in visual communication by producing colored traits that often evolve as intraspecific signals of quality. Identifying and quantifying melanins are therefore essential to understand the function and evolution of melanin‐based signals. However, the analysis of melanins is difficult due to their insolubility and the lack of simple methods that allow the identification of their chemical forms. We recently proposed the use of Raman spectroscopy as a simple, noninvasive technique that can be used to identify and quantify melanins in feathers and hairs. Contrarily, other authors later stated that melanins are characterized by a lack of defined Raman signals. Here, we use confocal Raman microscopy to confirm previous analyses showing that the two main chemical forms of melanins (eumelanin and pheomelanin) exhibit distinct Raman signal and compare different excitation wavelengths to analyze synthetic pheomelanin and natural melanins in feathers of different species of birds. Our analyses indicate that only laser excitation wavelengths below 1064 nm are useful for the analysis of melanins by Raman spectroscopy, and only 780‐nm laser in the case of melanins in feathers. These findings show that the capacity of Raman spectroscopy to distinguish different chemical forms of melanins depends on laser power and integration time. As a consequence, Raman spectroscopy should be applied after preliminar analyses using a range of these parameters, especially in fragile biological tissues such as feathers.